Superior QRS axis in ventricular septal defect. Issue 4 (October 1989) - Shaw, N J; Godman, M J; Hayes, A; Sutherland, G R
Abstract : The relation between the superior orientation of the QRS axis and the anatomical site of the defect in the ventricular septum in patients with a ventricular septal defect was studied. Of 1031 patients with a ventricular septal defect, 64 (6.2%) had a superior axis on their electrocardiogram. In 59% of these patients the defect was in the inlet portion of the ventricular septum or affected this area. None of the cases was classified as an isolated ventricular septal defect of the persistent atrioventricular canal type. While there is an association between a superior axis and perimembranous inlet ventricular septal defect, a superior QRS axis does not characterise a ventricular septal defect as being of the atrioventricular canal type.